The Strategic Role of The Police Baintelkam in Preventing Hoax and Disinformation in the 2024 Election - Amirul Fadel Kurniyanto; Riska Sri Handayani; Henny Saptatia Drajati Nugrahani (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
The 2024 elections are marked by serious challenges in the form of the spread of hoaxes and disinformation that could trigger social conflict and undermine public trust. In this situation, the Indonesian National Police's Intelligence and Security Agency (Baintelkam Polri) has a strategic role to play in early detection and prevention to maintain political stability and national security. This research seeks to investigate the strategic significance of the Baintelkam Polri in thwarting hoaxes and misinformation in the upcoming 2024 elections, assess the risks and obstacles presented by the dissemination of false information on online platforms, and appraise the efficacy of inter-sectoral partnerships in upholding political stability and the integrity of democracy. This study employs a descriptive qualitative method, with data collected through interviews, observations, and documentary studies. The findings reveal that: 1) The 2024 elections are vulnerable to the spread of hoaxes and disinformation, particularly through video content on platforms like YouTube and Facebook, targeting areas with low digital literacy and high social tension. These hoaxes have the potential to trigger social conflict and political polarisation; 2) Baintelkam Polri plays a strategic role in preventing hoaxes and disinformation during the 2024 elections through digital intelligence monitoring, mapping regional vulnerability indices, and educating the public on digital literacy. Through cross-sector collaboration and intelligence technology, Baintelkam Polri maintains security and social stability by ensuring that the democratic process runs safely and smoothly. These efforts strengthen public trust and minimise the negative impact of hoaxes and disinformation in the elections.